Residual soil nitrate as affected by giant reed cultivation and cattle slurry fertilisation - Ceotto, Enrico; Marchetti, Rosa; Castelli, Fabio (Italian Journal of Agronomy, 2018)
The residual soil nitrate (RSN) is the amount of nitrate which remains in soil profile after crop uptake has ceased, typically in the autumn. The RSN is prone to leaching and therefore poses serious environmental concerns, especially in areas with intensive livestock activities. Little is known about the ability of the energy grass giant reed in leaving low RSN. Such ability would add a desirable environmental benefit to giant reed cultivation. This article reports on snapshot measurements of RSN across soil profile in the autumn of three consecutive years: 2010, 2011 and 2012. Soil nitrate content was measured on soil samples collected from the soil layers 0-0.2 m, 0.2-0.4 m, 0.4-0.6 m and 0.6-0.8 m. The RSN of giant reed was compared with RSN of the energy crops sweet sorghum and poplar short rotation coppice (SRC). The three energy crops were treated with two fertilisation regimes: 0 kg N ha–1 (Control) and 20 mm of cattle slurry (CS20). Soil samples were also taken for a reference crop of winter wheat following winter wheat and receiving no N supply. Our findings for the three years of experiment can be summarised as follows: i) in case of the unfertilised Control, the three dedicated energy crops giant reed, sweet sorghum and poplar SRC left in soil profile in the autumn significantly lower amounts of RSN compared to the reference crop of wheat. Hence, all the three energy crops provided in similar manner the environmental benefit of leaving lower RSN; ii) in case of cattle slurry application the real advantage of giant reed cultivation became surprisingly evident. In fact, in three subsequent years the treatment giant reed CS20 never determined RSN significantly higher than RSN for giant reed Control. The RSN for giant reed with treatment CS20 was significantly lower than that the reference crop of wheat in all the three years. Unlike poplar SRC and sweet sorghum, giant reed exerted effective soil nitrate removal with a relatively high rate of cattle slurry application. Hence, this species can be regarded as suitable not only to utilise livestock effluents, but also to reduce the risk of nitrate pollution in many land use situations dealing with nitrogen surplus.